EFL teachers’ attitudes and competence in developing HOTS-based formative assessment - Rachmawati, Dwita Laksmita; Purwati, Oikurema (Universitas Muhammadiyah Sidoarjo, 2021)
Nowadays, Higher Order Thinking Skills have been a current trend and focus among teachers and researchers. However, there are still a few researchers who investigate HOTS and connect it with language assessment. This case study aimed to examine Indonesian English teachers' attitudes concerning the use of the HOTS-based assessment. This research has been qualitatively conducted with the aim to analyze the attitudes towards the utilization of the paradigm of HOTS in the creation of good language assessment. The data of this study were collected by using an interview and questionnaire. There are 20 teachers taking part in the study were purposely selected based on their experience and comprehension of the study's issue. The data of this study were analyzed by using descriptive qualitative. This study revealed that despite several situational constraints, all respondents shared their positive attitude to the principles of HOTS owing to several aspects. Despite the teachers' positive attitude towards the implementation of HOTS-based assessment, there was still a lack of knowledge about HOTS. This study suggested that more researchers portrayed teachers' competence in developing based assessment in English subject since HOTS is essential in the implementation of the 2013 curriculum. HIGHLIGHTS: The study addresses the current trend and focus on Higher Order Thinking Skills among teachers and researchers. Teacher as a “driver” in the classroom plays a crucial role in implanting HOTS for their students. Therefore, relevant training should be conducted progressively for English teachers, both pre-service and in-service teachers, to improve their knowledge to implement HOTS. Formative assessment can be employed as a “weapon” to promote the learners’ HOTS in this 2013 curriculum.